O discurso de resistência em meio à espetacularização do Festival Folclórico de Parintins - Cardoso, Jorcemara Matos (2016)
In Brazil, since the outbreak of the Modern Art Week in 1922, has been drawing a quest to discover which are the characteristic points that make the subject is Brazilian, feel belonging to a Brazilianness. It is true that throughout history, with its discontinuous points (Foucault, 1995), emerge speeches that make this identification is aflore in different ways. One would be the intense mass media of the manifestations of popular culture, this has increasingly been seen as an emblem of Brazilianness, as forms of identification of a people, starting from regional to a national identity (CRUZ, 2005). The 1990s will break in the Amazon making emerging parties like Ciranda in Manacapuru-AM; Çairé in Alter do Chão-PA; Bumba-meu-boi in São Luís, the Parintins Folklore Festival etc., to be seen and "potentiated" a local setting regional identity representations and, why not say, part of the national identity diversity. The identities before seen as solid, are now placed with malleable identities (Bauman, 2005). In particular, the Parintins Festival, now FFP, entering the field of visibility, we are moving in many more mídiuns, numerous shapes and positions on this folkloric manifestation, causing disputes, influencing saying, representations and memories. Put another way, it begins to be seen and constructed as a spectacle, in the sense that Debord (1997) gives this concept. The year 2013 emerges as a discursive event, with regard to the centenary of bumbás Parintins, celebrated on the 48th Festival of Parintins, in which we see the refresh memories, producing different effects of meaning. Therefore, believing that the identity and memory worked at the party are made, molded to the show, we made the following question: to what extent can see a resistance discourse amid the spectacle of the 48th Folkloric Festival of Parintins? Thus, we used a discourse analysis entitled French from Pêcheux (1998; 2007; 2009; 2010; 2012), which gives us the theme, mainly to reflect about ideological processes, materiality, linguistics, contradiction, which in our view is an important step to realize the strength of speech, as the speech another with which the subjects (for / against) identify which emerges in the official discourse, is marked on the tongue, causing updates , repetitions, silences. We bring to this dialogue, Michel Foucault (1995; 1999; 2004; 2010; 2014), especially regarding the perception of utterance, enunciation function, discursive formation, file, power relations which are the basis of its archaeological phase, showing -We do not the representation of discourse, but as the statements constitute speeches. It is this dialogue between Pêcheux and Foucault we build our analysis base. Another author important for our research is Courtine, which mobilized mainly their formulations about discursive memory both in his 1981 text, as its current reflections (2008, 2014) on the mobilization of memory and discursive formation. During the research, we found that: i) the effects of meaning production processes, about the ox-bumbá, are regulated by silences imposed by social relations involving the party today, as requirements of the cultural industry; ii) the feast of the manifestation of space, followed by the production and handling of identity and memory, gives rise to discourses of resistance, which show the spectacle of folkloric festival of Parintins; iii) the marginalized voices (Indian and black, above) existing power relations in the party auto start from the same place and are taking different paths due to the agency on the valuation of a culture on the other, making a reach upward as focus and the other being relegated to carnivalization; iv) space and be the party are built in this relationship between the assemblages in which the party is immersed and the constitution of these as objects of history; v) as memory production space, documentaries, media reports and advertisements glosses of a molded memory, producing not only a history of the horse, but also an identity connected to this memory. Understanding this folkloric manifestation by discursive bias, it was necessary, therefore, to see it as building speech taken as true at a time, in the area of your body, in the succession of events that brings out the speech / memory and not another ( a) instead of that subject, identity and memory are in a relationship of power, knowledge and strength being (re / in) meanings within the FFP.